The Impact of COVID-19 on Gametes and Endometrium: A Narrative Review - Karatas, Esra; Gunes, Ali Can; Temiz, Bilal Esat; Mumusoglu, Sezcan; Bozdag, Gurkan (Gynecology Obstetrics & Reproductive Medicine, 2023)
The Coronavirus disease 2019 (COVID-19) has been affecting our lives since December 19. Naturally, during the COVID-19 outbreak, it has become a point of interest whether severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection might affect oocyte, and sperm and influence the implantation during the assisted reproductive technology cycles. In the current narrative review, we aimed to scrutinize articles about SARS-CoV-2 infection and infertility concerning the safety of gametes and the endometrium. Whereas the available data suggest that SARS-CoV-2 interferes with various types of molecular pathways in the oocyte, spermatozoa, and endometrium, the lack of co-expression in angiotensin-converting enzyme 2 and transmembrane protease serine 2 in those cell lines theoretically avoid concerns by patients and reproductive endocrinologists. However, one should consider that those observations were based on a few case series and should be confirmed with further observational studies including a larger sample size with various clinic spectrums. Alternative pathways that can be utilized by the virus to invade gametes and individual differences in molecular expression are other potential limitations that should be considered.